Politik Hukum Pidana Terhadap Penanganan Tindak Pidana Pencurian dengan Kekerasan yang Terjadi di Jalanan Kota Medan - Sianturi, Jon Efendi; Marlina, Marlina; Siregar, Taufik (ARBITER: Jurnal Ilmiah Magister Hukum, 2020)
The occurrence of a crime generally occurs due to causes outside the law. The problem in this research is to find the cause of criminal theft with street violence in Medan city. Applying the formulation of Criminal Political Law Policy to the Crime of theft with Violence on the streets and knowing the effort to overcome the crime of theft with street violence in Medan City by Medan City Police Resort. The research method used is the normative juridical method, with the leper approach (library reseacrh) that collects the data source from literature literature. Factors causing violent crime in Medan City can be categorized of psychology of the perpetrator, external factors composed of environment, economy, victims. Efforts made by the Medan City Police Officers in Countering Crimes of Violence, Creating Police Stations as Public Complaints Facility